Efficient Vocal Melody Extraction from Polyphonic Music Signals - Yao, G.; Zheng, Y.; Xiao, L.; Ruan, L.; Li, Y. (Elektronika ir Elektrotechnika, 2013)
Melody extraction from polyphonic music is a valuable but difficult problem in music information retrieval. This paper proposes a system for automatic vocal melody extraction from polyphonic music recordings. Our approach is based on the pitch salience and the creation of the pitch contours. In the calculation of pitch salience, we reduce the peaks number of the spectral transform using a two-level filter and shrink the pitch range in accordance with the experiment to improve the efficiency of the system. In the singing voice detection, we adopt a three-step filter using the pitch contour characteristics and their distributions. The quantitative evaluation shows that our system not only keeps the overall accuracy compared with the state-of-the-art approaches submitted to MIREX, but also achieves high algorithm efficiency. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.4575